Pengaruh Kompleksitas Tugas dan Pengalaman Kerja terhadap Audit Judgment dengan Religiusitas sebagai Variabel Moderasi : (Studi Empiris pada Kantor Akuntan Publik di Kota Padang) - Pradipta, Putri; Fauzihardani, Eka (Universitas Negeri Padang, 2025)
This study aims to prove and analyze the influence of task complexity and work experience on audit judgment through religiosity as a moderating variable. This research was conducted on auditors affiliated with Public Accounting Firms spread across the Padang City area. The data collection technique used in this research was a survey, which was carried out by distributing questionnaires. The data analysis technique used was Moderating Regression Analysis (MRA) with the t-statistic test as a tool in testing the hypothesis. In accordance with the results of the hypothesis testing, it was found that task complexity had a negative effect on audit judgment, in addition, religiosity was proven to have a positive effect on auditor judgment, but task complexity did not affect audit judgment. Another important result that the researcher obtained was that religiosity was able to moderate the relationship between auditor experience and audit judgment, but religiosity was not able to moderate the relationship between task complexity and auditor judgment.